HUMANISTIC VALUES FOR CHILDREN IN ANDREW STANTON'S FINDING NEMO MOVIE (2003): A SOCIOLOGICAL APPROACH - HARTANI, MUGI (2011)
The major problem in this research paper is to explain how humanistic values reflected in Andrew Stanton's Finding Nemo movie are. The purposes of this research paper are to analyze Andrew Stanton's Finding Nemo Movie (2003) based on the structural elements of the movie. To describe Humanistic Values for Children reflected in Andrew Stanton's Finding Nemo Movie (2003) based on sociological approach. The object study is Finding Nemo movie that the screen play is by Andrew Stanton. It is using by sociological approach. In analyzing this study, the writer uses qualitative methodology of research and sociological approach. The Primary data source of this research is the movie Finding Nemo movie that the screen play is Andrew Stanton. The secondary data sources are book such as Sociology of Literature, Theory of Literature, and the other source that support the analysis. Having analyzed this research paper, the writer presents two conclusions. First, Finding Nemo in an animation movie produced in 2003 by Pixar Anination Studios Movie. Finding Nemo the movie, which was made in 2003 in USA, is directed and written by Andrew Stanton. In this movie each element of this movie has contribution with sociological's aspect. Second, in Finding Nemo movie the director reflects Humanistic Values through the major character. By this movie the director shows the humanistic values that can be find in this movie. It is directed to children and their parents. It can appeal to almost anyone, though. This story employs many techniques in order to persuade its audience into believing.